The Reception Theory And The Partial And Integrated Strategies Derived From It - heddad, hasna; bengana, hafida (El Omda in Linguistics and Discourse Analysis, 2025)
with the previous cognitive and technological advancements witnessed in the scientific knowledge arena today, it is essential for us to discuss the outcomes of interdisciplinary studies and what these studies have yielded in terms of benefits for science and the worlds . in this context , we have chosen the field of teaching and education as the most significant and sensitive point in the life of individuals and social classes. This study aims to define the most important procedural concepts adopted by reception theory and to present the key metacognitive strategies related to language teaching that stem from reception theory in order to clarify their significance and emphasize the necessity of utillizing them to improve educational curricula and their content.